Tradisi dalam Wawasan Buya Syafii Pasca Titik Kisar - Putra, Riki Dhamparan (MAARIF Institute, 2023)
Religion, in this note, is seen as tradition. It is a historical product of the application of intellectual ideas that rose to sacred status equal to religion. According to Fazlur Rahman, this was an error that stemmed from the poor scientific discipline of the Muslim intellect in the early phase of the Muslim tradition. Buya Ahmad Syafii Maarif follows Fazlur Rahman’s views and strengthens them through a further review of the process of inheritance of this tradition and attempts to explain that the contemporary problems of the Muslim world still rest on the same base of mistakes; traditions that are sacred as a religion - Thus it is forbidden to change even though the norms in that tradition are already weak and no longer relevant to be used to fortify the Muslim world.